The Effect of Zikir Therapy on Reducing Anxiety in Children with Cancer: A Case Study of Pediatric Cancer Patients at the C-Four Shelter, Kuta Alam, Banda Aceh - Rahmadani Handoyo, Raihan; Ismiati, Ismiati; Jarnawi, Jarnawi (Rifa'Institute, 2025)
This study investigates the effect of dhikr therapy in reducing anxiety among children with cancer residing at the C-Four shelter in Banda Aceh. The objective is to explore whether dhikr can serve as an effective spiritual intervention to manage anxiety in pediatric cancer patients undergoing chemotherapy. A quasi-experimental method was employed using a pretest-posttest control group design. The study involved 10 children divided into an experimental group receiving dhikr therapy and a control group without intervention. The Hamilton Anxiety Rating Scale (HARS) was used to measure anxiety levels before and after the intervention. Results showed a decrease in anxiety severity in the experimental group, with one subject shifting from “very severe” to “severe,” while no change was observed in the control group. However, statistical analysis using the Wilcoxon and Mann-Whitney tests revealed no significant difference (p = 0.317 and p = 1.000, respectively). The findings suggest that while dhikr therapy has the potential to reduce anxiety levels, a longer intervention period and broader sample size may be required for statistically significant results. In conclusion, dhikr therapy may serve as a supportive spiritual approach to reduce anxiety in children with cancer during treatment